Connecting Students by Integrating the 3D Virtual and Real Worlds: We Need 3D Open Source Spaces to Keep Socialization, Communication and Collaboration Alive - Reiners, Torsten; Dreher, Carl; Buttner, S.; Naumann, M.; Visser, L. (AACE - Association for the Advancement of Computing in Education, 2009)
Picture a world where imagination is the only limit; a world that stimulates students to learn, communicate, play and grow. The emergence of 3D Virtual Worlds has made this a virtual reality. Until recently this virtual experience has been separated from the real world by the limitations of software (proprietary systems), and constraints of hardware and networks (stationary consoles and network connections). Such separation limits the pedagogical utility that 3D Spaces can offer students. This article peeks around the corner of innovation by exploring a number of emergent open source developments that integrate the 3D Virtual and Real Worlds into a seamless reality, one that enhances pedagogical opportunities by integrating the practical and vocational actuality of the real world with the technical and imaginable possibilities of the Virtual Worlds. These possibilities are explored with reference to recent developments, pedagogical theory, and case studies in various open source 3D Virtual Worlds.